To the 100-th Anniversary of Kirill Borisovich Tolpygo’s Birthday (May 3, 1916–May 13, 1994) - Glinchuk, M. D.; Loktev, V. M.; Pashitskii, E. A.; Pashkevich, Yu. G.; Ryabchenko, S. M.; Soskin, M. S.; Sugakov, V. I.; Tolpygo, S. K.; Shatalov, V. M. (Publishing house "Academperiodika", 2019)
-